Keterbukaan Diri dan Pembentukan Keakraban Generasi Z dalam Komunitas Thrifting Tabanan: Perspektif Teori Penetrasi Sosial - I Putu Yoga Pratama; Irma Suryanti; Nuning Indah Pratiwi; Putu Suparna (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the process of self-disclosure and the formation of intimacy among Generation Z members in the thrifting community in Tabanan through the perspective of Social Penetration Theory. Generation Z, who grew up in the digital era, is known for open, expressive, and adaptive interpersonal communication styles within new social environments. The thrifting community, which focuses on buying and selling secondhand items and sharing interests in sustainable lifestyles, provides a social space that facilitates meaningful interactions among members. This research employs a qualitative approach using in-depth interviews with several active members of the community. The findings reveal that self-disclosure serves as the main foundation for building closeness and mutual trust among members. The process of social penetration occurs gradually, starting from light conversations about shared interests to more personal and emotional discussions. The intimacy developed strengthens solidarity, a sense of togetherness, and group identity. In addition to serving as a communication tool, self-disclosure also functions as a mechanism for fostering empathy and mutual understanding among members. These findings indicate that Social Penetration Theory is relevant in explaining the interpersonal communication dynamics of Generation Z in thrifting communities, where social relationships grow through openness, trust, and intimacy.